A 5-year audit of major maxillofacial surgeries at Usmanu Danfodiyo university teaching hospital, Nigeria - Adebayo Aremu Ibikunle; Abdurrazaq Olanrewaju Taiwo; Ramat Oyebunmi Braimah (BMC, 2018)
Abstract Background There is a paucity of data on the pattern of oral and maxillofacial surgeries done in Nigeria. Despite the rising prominence of oral and maxillofacial surgery as a specialty in our immediate environment, no published audit of the surgeries performed exist. This study aims to present the pattern and types of major surgeries done by oral and maxillofacial surgeons in our hospital as well as the indications for such surgeries. It is hoped that the findings will assist in formulating informed policies and improving healthcare delivery. Methods A review of hospital records of all patients who had major oral and maxillofacial surgeries at Usmanu Danfodiyo University Teaching Hospital from January, 2013 to August, 2017 was done. Descriptive statistics such biodata, indication for surgery and type of surgery were recorded and analyzed using the IBM SPSS statistics for windows version 20 (Armonk, NY: IBM Corp) software. Results One hundred and forty six individuals who underwent 158 major surgeries under general anaesthesia were included. There were 82 males and 64 females, giving a male/female ratio of 1.3: 1. The ages ranged from 3 months to 81 years [median of 33 years]. Tumours and tumour-like lesions were the major indications for surgery [85 (58.2%)]. The most commonly performed surgery was mandibulectomy [31 (19.6%)], followed by Open Reduction and Internal Fixation (ORIF) [29 (18.4%)]. Conclusion Major oral and maxillofacial surgeries are common in our environment. The frequencies of these surgeries can increase with better healthcare financing and universal availability of health insurance schemes. Efforts aimed at reducing the incidence of tumours should be instituted.